The European Union between Intergovernmentalism and 'Shared and Responsible Sovereignty': The Haptic Potential of EMU's Institutional Architecture (The Government and Opposition/Leonard Schapiro Lecture, 2016). Issue 3 (28th December 2016) - Piattoni, Simona
Abstract : The article starts from a critique of the widespread assumption that intergovernmentalism is not only the more practical but also the more democratic way of handling the current European crises – and particularly the euro crisis – to argue for the need to rethink the working and the definition of democracy in the current heightened interconnectedness of political organization. It suggests that perceiving European citizens as being separated into distinct state communities stands in the way of a full appreciation of the externalities, hence of the reciprocal responsibilities, that they owe each other and turns apparently democratic decisions into potential acts of domination, as theorized by both Pettit (1997) and Bohman (2006). It suggests that we should embrace a more encompassing and dialogical notion of democracy which translates Pallasmaa's (2012) notion of hapticity from the field of physical architecture to that of institutional architecture. It concludes by suggesting that there are already institutional architectures in the EU which lend themselves to a haptic declension, for example the European Semester.